Design and evaluation of mechanical properties of cement grouted bituminous mixes (CGBM). (1st February 2021) - Shukla, Manoj; Gottumukkala, Bharath; Nagabhushana, M.N.; Chandra, Satish; Shaw, Amit; Das, Shankh
Highlights: Design of cement grouted bituminous mixes: Binder content, Compaction effort and water content in the grout. Effect of aggregate gradation on design of grout in the mixture is analysed. Variation of flowability of grout with respect to mixing time and water content is analysed. X-ray Micro Computed Tomography test was used to analyse the air voids content and their interconnectivity in the mix. Field Performance of CGBM sections is evaluated by Falling weight deflectometer and results compared with control section. Abstract: Cement Grouted Bituminous Mix (CGBM) is a composite paving mix comprising of a high voids bituminous mix impregnated with a cementitious grout. This type of mix is suitable for wearing course. The high void mix is prepared by selecting a suitable aggregate gradation, binder content and compaction effort to result in sufficiently optimized air void content. Six different cement grouted bituminous mixes prepared with varying aggregate gradations, compaction effort and grout composition are evaluated in this study. To design an acceptable bituminous mixture skeleton for CGBM, the effects of aggregate gradation on resulting grouting in the mixture are analysed. Results showed that the extent of grouting in bituminous mixture skeleton is affected by its internal void interconnectivity, structure and size of pores rather than the initial void volume. A mix design approach is developed to prepare the bituminous mix skeleton for CGBM. The study also examines the issues related to the design of aggregate gradation and cementitious grout and evaluates the properties of cement grouted bituminous mixes. For laboratory samples, X-ray Micro Computed Tomography (XRμCT) test was used to analyse the air voids content and their interconnectivity. Test sections were laid in field and monitored for their performance. Field core samples extracted showed effective full depth grouting. Falling Weight Deflectometer test was also conducted to check the in-situ moduli of CGBM mix.